2021
DOI: 10.1021/acs.energyfuels.0c04268
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of the Effect of Porous Media Permeability on the Decomposition Characteristics of Natural Gas Hydrate at the Core Scale

Abstract: As a new type of clean energy, natural gas hydrates are widely distributed in ocean and permafrost. Moreover, it is important to understand the gas production characteristics of gas hydrate resources for the commercial exploitation in the future. The natural gas produced from hydrate bearing sediment is influenced by heat transfer, multiphase flow, and hydrate decomposition phase transition in the reservoir. This paper investigates the impact of permeability on the decomposition characteristics of hydratebeari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…There are six reviews covering a wide range of aspects related to methane hydrates targeting resource potential, production methods (depressurization and CH 4 /CO 2 exchange), exploration activities, sand management, and hydrate properties . The original research articles pertaining to the topic of hydrates cover a wide spectrum of areas, from numerical modeling, ,,, hydrate properties and characterization, ,,,, hydrate equipment ,,, to fluid production analysis, , ,, etc.…”
Section: Hydratementioning
confidence: 99%
“…There are six reviews covering a wide range of aspects related to methane hydrates targeting resource potential, production methods (depressurization and CH 4 /CO 2 exchange), exploration activities, sand management, and hydrate properties . The original research articles pertaining to the topic of hydrates cover a wide spectrum of areas, from numerical modeling, ,,, hydrate properties and characterization, ,,,, hydrate equipment ,,, to fluid production analysis, , ,, etc.…”
Section: Hydratementioning
confidence: 99%
“…In the evaluation of NGH reservoir productivity, seepage and thermal conductivity parameters are the most critical technical parameters. This is mainly because they can respectively reflect the gas production efficiency and decomposition rate , to a certain extent. According to previous studies, in terms of permeability, Kumar et al measured the absolute permeability of filled porous media under different hydrate saturations and found that the presence of a hydrate phase will significantly reduce the intrinsic permeability of sediments, pointing out that in addition to traditional oil and gas storage, the study of permeability characteristics of HBS reservoirs should be regarded as an independent direction.…”
Section: Introductionmentioning
confidence: 99%
“…Natural gas hydrates (cage compounds) are transparent or translucent solid compounds formed by hydrogen bonding of guest molecules such as methane gas or carbon dioxide with water. In the natural environment, gas hydrate exists stably in the form of methane and water crystallization under low-temperature and high-pressure conditions, which is also widely distributed in offshore areas and permafrost zones. Under the background of the exhaustion of traditional fossil resources and continuously increasing energy demand, as a clean and efficient unconventional fossil energy with wide distribution and large reserves, natural gas hydrate can provide critical support for solving the energy shortage problem. , However, the geological characteristics of hydrate-bearing sediments are complex and the sedimentary environment is sensitive, , and the exploitation of hydrate is accompanied by the decomposition of hydrate. , The decomposition of hydrate will reduce the sediment strength, which will lead to landslide, deposition, and another marine geological disaster. Therefore, the study of the mechanical characteristics of methane hydrate-bearing sediment (MHBS) under triaxial stress is of great importance to the safety and stability exploitation and commercialization of hydrate engineering …”
Section: Introductionmentioning
confidence: 99%